Stress analysis of anisotropic hybrid composite plates with loaded holes - Minh, Nguyen Cong; Quan, Nguyen Hoang; Thuong, Nguyen Van (Vietnam Journal of Mechanics, 2026)
In this paper, a stress analysis of hybrid anisotropic composite plates with loaded holes is performed using the boundary-based finite element method (BFEM). Here, the hybrid composite plates may consist of different anisotropic elastic materials. To apply the BFEM, we divide the plate into different regions, each of which is made of different anisotropic elastic constants. The BFEM combines the boundary elements in each region into a single finite element and assembles them following the rules of the finite element method. This method, therefore, does not require volumetric meshing, which is beneficial for meshing and computational costs. The BFEM can be applied to general anisotropic hybrid elastic plates and various loaded hole situations, e.g., pressurized holes or prescribed displacements on the holes. With the BFEM, numerical examples are performed. The numerical results will be used for verification and parametric study purposes. In the verification, we compare the results obtained by the BFEM with those obtained by other available solution methods. The parametric studies investigate the effects of the anisotropic material properties and applied pressurized loads/displacements on the stress distribution around the hole.